Bibliometric Analysis of Competitive Advantage - Loso Judijanto (West Science Social and Humanities Studies, 2026)
Competitive advantage has emerged as an essential aspect of strategic management that helps firms build their capabilities and sustain themselves in volatile market conditions. In this study, an attempt is made to conduct a bibliometric analysis to investigate the intellectual structure, trends in research, key contributors, and emerging themes in competitive advantage research. The data was collected from Scopus database using the keywords "competitive advantage" and analyzed using VOS viewer to conduct co-occurrence analysis, citation analysis, co-authorship analysis, institutional collaboration analysis, and country collaboration mapping. The results show that competitive advantage and competition are the two core themes that have close linkages with innovation, knowledge management, sustainability, supply chain management, marketing, and organizational performance. Based on citation analysis, some of the key theories such as dynamic capabilities, absorptive capacity, corporate social responsibility, sustainable business model, and strategic positioning are found to significantly influence the field of competitive advantage. The collaboration analysis demonstrates that the United States, the United Kingdom, China, Australia, and other countries serve as major contributors to the global research network, supported by influential scholars and academic institutions. Furthermore, the thematic evolution indicates a transition from traditional strategic management perspectives toward contemporary approaches emphasizing digital transformation, sustainability, organizational agility, and capability development. This study contributes to the literature by providing a comprehensive mapping of competitive advantage research development and identifying potential future directions for scholars, particularly in integrating technological innovation, sustainable practices, and dynamic organizational capabilities to achieve long-term competitiveness.